Acute Interstitial Pneumonia (AIP): Relationship to Hamman-Rich Syndrome, Diffuse Alveolar Damage (DAD), and Acute Respiratory Distress Syndrome (ARDS) - Mukhopadhyay, Sanjay; Parambil, Joseph G. (Seminars in Respiratory and Critical Care Medicine, 2012)
Acute interstitial pneumonia (AIP) is a term used for an idiopathic form of acute lung injury characterized clinically by acute respiratory failure with bilateral lung infiltrates and histologically by diffuse alveolar damage (DAD), a combination of findings previously known as the Hamman-Rich syndrome. This review aims to clarify the diagnostic criteria of AIP, its relationship with DAD and acute respiratory distress syndrome (ARDS), key etiologies that need to be excluded before making the diagnosis, and the salient clinical features. Cases that meet clinical and pathologic criteria for AIP overlap substantially with those that fulfill clinical criteria for ARDS. The main differences between AIP and ARDS are that AIP requires a histologic diagnosis of DAD and exclusion of known etiologies. AIP should also be distinguished from “acute exacerbation of IPF,” a condition in which acute lung injury (usually DAD) supervenes on underlying usual interstitial pneumonia (UIP)/idiopathic pulmonary fibrosis (IPF).
Keywords: acute interstitial pneumonia; acute lung injury; acute respiratory distress syndrome; diffuse alveolar damage